Protonation of palmitic acid embedded in DPPC lipid bilayers obscures detection of ripple phase by FTIR spectroscopy - Pem, Barbara; Pišonić, Marina; Momčilov, Marina; Crnolatac, Ivo; Brkljača, Zlatko; Vazdar, Mario; Bakarić, Danijela (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2024)
The transformation of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) lipid bilayers from the gel (Lβ') to the fluid (Lα) phase involves an intermediate ripple (Pβ') phase forming a few degrees below the main transition temperature (Tm). While the exact cause of bilayer rippling is still debated, the presence of amphiphilic molecules, pH, and lipid bilayer architecture are all known to influence (pre)transition behavior. In particular, fatty acid chains interact with hydrophobic lipid tails, while the carboxylic groups simultaneously participate in proton transfer with interfacial water in the polar lipid region which is controlled by the pH of the surrounding aqueous medium. The molecular-level variations in the DPPC ripple phase in the presence of 2% palmitic acid (PA) were studied at pH levels 4.0, 7.3, and 9.1, where PA is fully protonated, partially protonated, or fully deprotonated. Bilayer thermotropic behavior was investigated by differential scanning calorimetry (DSC) and Fourier-transform infrared (FTIR) spectroscopy which agreed in their characterization of (pre)transition at pH of 9.1, but not at pH 4.0 and especially not at 7.3. Owing to the different insertion depths of protonated and deprotonated PA, along with the ability of protonated PA to undergo flip-flop in the bilayer, these two forms of PA show a different hydration pattern in the interfacial water layer. Finally, these results demonstrated the hitherto undiscovered potential of FTIR spectroscopy in the detection of the events occurring at the surface of lipid bilayers that obscure the low-cooperativity phase transition explored in this work.
Keywords: protony; Lipid Bilayers; pH-dependent (de)protonation; lipidové dvojvrstvy; Calorimetry, Differential Scanning; Hydrogen-Ion Concentration; teplota; Phase Transition; 1,2-dipalmitoylfosfatidylcholin; Molecular Structure; Spectroscopy, Fourier Transform Infrared; diferenciální skenovací kalorimetrie; DSC and FTIR spectroscopy; Temperature; molekulární struktura; spektroskopie infračervená s Fourierovou transformací; Palmitic Acid; 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) lipid bilayers; změna skupenství; Ripple phase; Protons; kyselina palmitová; Palmitic acid (PA); koncentrace vodíkových iontů; 1,2-Dipalmitoylphosphatidylcholine